Evidence-based practice in LIS: the systematic review - Wiley, Claire Walker, author; Houlihan, Meggan, author; Click, Amanda B., author (Colorado State University. Libraries, 2020)
This chapter provides an overview of the method, guidelines for study design, and the lessons we have learned during our own research experiences. Even if a systematic review is not an appealing or appropriate method for some practitioner-researchers, many librarians may find themselves in a support role for a systematic review conducted by other researchers or faculty members. Health sciences librarians and academic librarians are most likely to provide support for this method and may find this chapter particularly useful.